How to Improve Soil Anti-adhesion by studying the micro relief of the cuticle surface of digging beetles: Exploring the gromphas lacordairii (Oken, 1834) pronotum - Setten, Lorena (2024)
Some years ago, Tesouro et al. (2018) proposed a possible solution for decreasing adhesion of the soil particles to the surface components of agricultural machinery based on a biological system (biomimetic studies). This has the purpose of reducing the drawing force on the tool with a consequent reduction in fuel consumption. They analyzed the micro topography (micro relief) of the cuticular surface of the Diloboderus abderus (Coleoptera, Scarabaeidae) using a scanning electron microscope (SEM).